Functional consequences of mitochondrial mismatch in reconstituted embryos and offspring - Kumiko TAKEDA (The Society for Reproduction and Development, 2019)
Animal cloning technology has been developed to produce progenies genetically identical to a given donor cell. However, in nuclear transfer protocols, the recipient oocytes contribute a heritable mitochondrial genomic (mtDNA) background to the progeny. Additionally, a small amount of donor cell-derived mitochondria accompanies the transferred nucleus in the process; hence, the mtDNAs of two origins are mixed in the cytoplasm (heteroplasmy) of the reconstituted oocyte. Herein, I would like to introduce some of our previous results concerning five key considerations associated with animal cloning, including: mtDNA heteroplasmy in somatic cell nuclear transferred (SCNT) animals, the variation in the transmission of mtDNA heteroplasmy to subsequent generations SCNT cows and pigs, the influence of mtDNA sequence differences on mitochondrial proteins in SCNT cows and pigs, the effects of the introduction of mitochondria derived from somatic cells into recipient oocytes on embryonic development, and alterations of mtDNA heteroplasmy in inter/intraspecies nuclear transfer embryos.